The Commercialisation of Polish Socialist Heritage – Tourist, Entertainment and Collectable Products and Souvenirs in the Vintage Style - Płaziak, Monika (Przedsiębiorczość - Edukacja, 2020)
On the Polish market, original and stylised products referring to the era of socialism are becoming popular. These are mainly cultural and entertainment products with both everyday and artistic items being offered and purchased on online auction portals while the production of sentimental memorabilia from the period of the Polish People’s Republic is also being developed. At the same time, the growing interest in Poland as a tourist destination among both domestic and foreign tourists is the reason for the increasing curiosity of its socialist past. Therefore, tourist offers based on relics of that era are increasingly being created on the domestic tourist market, however, the quality of these products and services sometimes raises concerns over the quality of the message that they carry. The main question is whether this is only a simplified message based on stereotypes which give the recipient only a truncated and shallow picture of Poland’s difficult past. This article discusses the main trends and the conditions necessary for the creation of services and products based on relics of socialism in Poland and is based on sources from Polish and foreign literature, both academic and professional, as well as the websites of businesses and institutions creating such market offers.